Loss of ASD-related molecule Cntnap2 affects colonic motility in mice - Robinson, Beatriz G.; Oster, Beau A.; Robertson, Keiramarie; Kaltschmidt, Julia A. (Frontiers in Neuroscience, 2023)
Gastrointestinal (GI) symptoms are highly prevalent among individuals with autism spectrum disorder (ASD), but the molecular link between ASD and GI dysfunction remains poorly understood. The enteric nervous system (ENS) is critical for normal GI motility and has been shown to be altered in mouse models of ASD and other neurological disorders. Contactin-associated protein-like 2 (Cntnap2) is an ASD-related synaptic cell-adhesion molecule important for sensory processing. In this study, we examine the role of Cntnap2 in GI motility by characterizing Cntnap2’s expression in the ENS and assessing GI function in Cntnap2 mutant mice. We find Cntnap2 expression predominately in enteric sensory neurons. We further assess in vivo and ex vivo GI motility in Cntnap2 mutants and show altered transit time and colonic motility patterns. The overall organization of the ENS appears undisturbed. Our results suggest that Cntnap2 plays a role in GI function and may provide a molecular link between ASD and GI dysfunction.